Maslahah-Based Protection of Fund Recipients in Fintech Lending Through Empowerment and Justice - Noor, Afif; Maskur, Ali; Kholiq, Arifana Nur; Rurkinantia, Aisa; Saifudin, Saifudin; Adila, Arina Hukmu; Maruf, Maruf (El-Mashlahah, 2025)
The rapid growth of fintech lending in Indonesia requires adequate regulation and protection for consumers, especially fund recipients, who face high risks such as intimidation and sexual harassment, high-interest charges, and misuse of personal data by fintech lending platforms. For this reason, protecting fund recipients is a primary need because it involves protecting life and property, which is integral to the benefit of maqashid sharia. The main objective of this research was to detail the concepts of empowerment and justice as pillars of protection for fund recipients in fintech lending from a maslahah perspective. The research used normative juridical methods with statutory and conceptual approaches and analyzed secondary data from document studies in a descriptive qualitative. The results showed that empowerment and protection of fund recipients in fair fintech lending align with the principle of maslahah, contribute positively to the welfare of society, and support the growth of a sustainable fintech lending industry ecosystem, and offering hope for a better future.